2010
DOI: 10.1016/j.heares.2010.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Polarity effects on neural responses of the electrically stimulated auditory nerve at different cochlear sites

Abstract: Three experiments studied the effect of stimulus polarity on the Electrically Evoked Compound Action Potential (ECAP) obtained with the masker-probe paradigm on different sites along the cochlea in cochlear implant users. Experiment 1 used a biphasic cathodic-1st (BIC) masker and showed that ECAP N(1) peak latencies were longer for BIC than for biphasic anodic-1st (BIA) probes on all electrodes under test. Both the latency of each probe as well as the latency difference between BIA and BIC probes increased whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
106
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 75 publications
(119 citation statements)
references
References 41 publications
(76 reference statements)
11
106
1
1
Order By: Relevance
“…Following the results by Macherey et al (2008) and Undurraga et al (2010) obtained in MP mode, the present results show that BP þ 3 PS, RPS and SYM-IPG maskers strongly excited AN fibers close to the masker electrode that delivered the effective anodic pulse. Macherey et al (2010) measured forward-masking excitation patterns in human CI users.…”
Section: Polarity Sensitivitysupporting
confidence: 85%
See 3 more Smart Citations
“…Following the results by Macherey et al (2008) and Undurraga et al (2010) obtained in MP mode, the present results show that BP þ 3 PS, RPS and SYM-IPG maskers strongly excited AN fibers close to the masker electrode that delivered the effective anodic pulse. Macherey et al (2010) measured forward-masking excitation patterns in human CI users.…”
Section: Polarity Sensitivitysupporting
confidence: 85%
“…Their results showed that anodic stimulation was necessary for an ECAP to be observed. Further research demonstrated that this finding is generalized along the cochlea (Undurraga et al, 2010). However, it may be that different stimulation modes (see Sec.…”
Section: Polarity Sensitivitymentioning
confidence: 76%
See 2 more Smart Citations
“…However, caution is required as anodic first stimulation was applied only twice per subject. A difference in tinnitus suppression between cathodic and anodic first charge-balanced electrical stimulation was initially expected as prior studies showed that anodic stimulation could be more sensitive than cathodic stimulation [Undurraga et al, 2010[Undurraga et al, , 2013Carlyon et al, 2013]. The cathodic phase is thought to stimulate the peripheral process while the anodic phase probably excites the nerve fibers more centrally [Rattay et al, 2001].…”
Section: Effect Of Polaritymentioning
confidence: 99%